Effectiveness and Timing of Congenital Nasolacrimal Duct Obstruction Probing: a Systematic Review: Oral Presentation - Observational Study - General practitioner - Kharisma Zatalini Giyani; Dewi Alya Winarto; Julie Dewi Barliana (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Most congenital nasolacrimal duct obstruction (NLDO) cases could resolve spontaneously or only require minimal conservative treatment. In unresolved cases, lacrimal probing is considered a primary treatment; however, no consensus on the best timing to perform probing is available. Therefore, this study aims to compare the effectiveness of immediate probing with deferred probing and to assess the best time to perform primary probing. Methods : A search for relevant literature was performed on four electronic databases: PubMed, Cochrane Library, EMBASE, and Scopus with predetermined keywords. The inclusion criteria consist of systematic reviews, RCTs, and prospective/retrospective studies published between 2013-2023 regarding lacrimal probing as an intervention for congenital NLDO. Results : We included seven studies. Three studies compared immediate and deferred probing, while four focused on the success rate of probing for NLDO at various age groups. Studies suggest immediate and deferred probing had a comparable effectivity in treating NLDO; however, one systematic review suggests immediate probing was superior to deferred probing. Studies also demonstrate that the success rate of probing declines with age. Lacrimal probing performed on NLDO patients under 12 months old had a success rate of more than 80%. Conclusion : Despite findings of comparable effectiveness between immediate and deferred probing, probing performed at a younger age yielded a higher success rate. This suggests that doctors should consider the patient's age at diagnosis to decide between immediate and deferred probing. Further evidence is needed to determine cut-offs for the best time to perform primary probing.